Regulation of casein micelles dissociation by sodium tripolyphosphate to improve gel properties as stabilizers and protein fortifier for high-protein yogurt - Zi-Ying Zhao; Zi-Wei Liu; Bo-Kang Yu; Ying-Chao Qiu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Within-species phenotypic resistance rather than community turnover tracks antimicrobial usage in Staphylococcus aureus on swine farms - So Hee Park; Jin Gyeong Jeong; Acme Afrin Jahan; Mu Sun Lee; Jeong Yoon Kang; Junsik John Kim; Bo-Youn Moon; Suk-Kyung Lim; Gihan Lee; SeungMuk Yu; Jin-Kyung Hong; Keunje Yoo; et al. (Environmental Pollution, 2026)

WDS-Modality: A Physics-Informed Multi-Modal Agent Framework for Resilient Water Distribution System Assessment Using Large Language Models without Fine-tuning - Tianwei Mu; Yue Wang; Manhong Huang; Mingzhe Yuan; Dan Xue; Wenhong Wang; Hui Yang; Jun Li; Bo Zhou (Water Research, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Enhanced biomethane production associated with olivine-stimulated CO2 reduction in petroleum reservoir production water - Muhammad Javed; Muhammad Irfan; Le-Gang Chen; Bo Fang; Bo-Wen Wang; Ghulam Dastgir; Muhammad Kashif Javed; Lei Zhou; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Tannic acid protects against lapatinib-induced hepatotoxicity by inhibiting cathepsin activity and repairing lysosomal membrane permeabilization - Yuan Mu; Zengyue Pan; He Zhao; Xiangliang Huang; Nini Zhang; Zhifei Xu; Bo Yang; Qiaojun He; Xiaochun Yang; Peihua Luo; Hao Yan (Toxicology and Applied Pharmacology, 2026)

Methanotrophs and co-occurring microbial taxa: Genomic potential for carbon, nitrogen, and sulfur cycles in newly formed high-altitude proglacial lakes - Meiqi Huang; Shengjie Li; Guangli Mu; Xiaodong Li; Qing Yang; Bo Shao; Qianggong Zhang; Yindong Tong (Environmental Research, 2026)

TME-activated MXene nanoheterojunctions engineer cancer cells through phototherapy and metabolic interference for enhanced cuproptosis and immunotherapy - Hui Li; Jie Geng; Min Mu; Susu Xiao; Chenqian Feng; Lihua Zhou; Yuanxiang Wang; Wei Yu; Rangrang Fan; Bo Han; Gang Guo (Chemical Engineering Journal, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Water droplets in crude oil: A new window into microbiome and microbial activity in subsurface oil reservoirs - Qiao-Hui Wang; Yi-Fan Liu; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

A biocompatible catalytic benzyl decaging enables activation of salicylic acid-dependent defense responses in plants - Yanhao Hu; Bo He; Mian Wei; Zhengxi Xiong; Yalin Mu; Ping Chen; Wang Chen; Jiahao Wang; Wei Yan; Yonghao Ye (Chemical Engineering Journal, 2026)

Precision design of hydrogel polymer nanoparticles: How side-chain spatial arrangement and length matching govern antibacterial activity, physiological robustness, and selectivity - Weixiang Zhang; Weicheng Tang; Bo Li; Shiqi Lin; Mu Yuan; Lei Su; Wenfeng Tan; Gailing Yuan; Mingming Liu (Chemical Engineering Journal, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Artificial Intelligence for Atmospheric and Oceanic Forecasting and Research: A Fudan University Perspective - Guokun Dai; Hao Li; Mu Mu; Guihua Wang; Bo Qin; Xiaohui Zhong; Feng Zhang; X. San Liang (Advances in Atmospheric Sciences, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Coupled atmosphere-ocean data assimilation for enhanced medium-range prediction of the North Atlantic Oscillation - Bin Mu; Zijun Zhao; Shijin Yuan; Bo Qin; Guokun Dai (Science China Earth Sciences, 2026)

Construction of a Ni/Semi-coke catalyst via a NiCl2-Lactic acid deep eutectic solvent for upgrading coal pyrolysis tar - Haozhao He; Tao Wang; Qu Zhang; Bo Li; Xianze Wang; Wenyan Mu; Dongling Wu (Fuel, 2026)

Enabling long-cycle-life high-voltage calcium metal batteries with fluorinated alkoxyborate-based CaNa hybrid electrolytes - Xinyue Li; Shuangshuang Cui; Bin Chen; Xiaoke Mu; Dechen Zeng; Hongkun Wang; Yang Wang; Bo Peng; Tianyu Zheng; Dianxing Ju; Aobing Du; Zhenyou Li; et al. (Chemical Engineering Journal, 2026)

An Integrated Physics-Informed Multi-Perturbation Framework for Scalable and Interpretable Leakage Detection in Water Distribution Networks - Feiyu Duan; Tianwei Mu; Bo Zhou; Baokuan Ning; Haoqiang Tan (Water Resources Management, 2026)

Microbial Perspective: Regulatory Mechanisms of Interactions Between Microplastics and Dissolved Organic Matter on Greenhouse Gas Emissions in Aquatic Ecosystems - Mengxin Xu; Meiqi Huang; Shuang Liu; Jinze He; Feng Zhao; Bo Shao; Guangli Mu; Hongyang Cui; Panpan Cui; Yingxin Zhao; Yiwen Liu; Xiaoyu Cui; et al. (Global Change Biology, 2026)
Microplastic (MP) pollution may influence aquatic greenhouse gas (GHG) emissions by altering dissolved organic matter (DOM)–microbe coupling, yet reported effects remain inconsistent across ecosystems and exposure regimes. Here, we synthesized evidence from 16 studies to quantify the net effects of MPs on CO 2 , CH 4 , and N 2 O fluxes under ambient DOM conditions. Our meta‐analysis indicates that MP exposure significantly increases CO 2 emissions and decreases N 2 O fluxes, whereas CH 4 responses show a non‐significant positive trend with high variability. Exposure duration and polymer identity emerge as key moderators, indicating that MP effects are context‐dependent rather than uniform. Short‐term exposure tends to suppress carbon mineralization, whereas long‐term exposure is more often associated with GHG production, consistent with a time‐dependent trajectory potentially shaped by polymer aging. Mechanistically, this pattern may reflect initial DOM adsorption and humification that reduce substrate availability, followed by the release of bioavailable MP‐derived compounds that may stimulate microbial respiration, methanogenesis, and denitrification. Overall, MPs reshape aquatic carbon and nitrogen cycling within the overarching framework of DOM, which may ultimately influence GHG emissions under certain conditions. These findings provide a quantitative basis for reconciling conflicting observations and improving predictions of the climate relevance of MP pollution in aquatic ecosystems.

Sequential release of photodynamic hybrid HOFs and CeO₂ via a bilayer dynamic SIS hydrogel for periodontitis therapy - Shiqing Ma; Yujia Xiao; Yang Yu; Xiaotong Liu; Jiayin Deng; Yilin Yang; Shiyu Yao; Beibei Ma; Yo Shibata; Jun Zhou; Bo Zhao; Yuzhu Mu (Chemical Engineering Journal, 2026)

The Potential Drug Target (Glycolysis Pathway) of the Spore Stage of the Pathogen Enterocytozoon hepatopenaei in Shrimp Farming - Bo Zhu; Juan Feng; Dong Qian; Ping Zhuang; Changkao Mu; Jiong Chen; Rongrong Ma (Fishes, 2026)
Enterocytozoon hepatopenaei (EHP) is a specialized parasitic microsporidian that causes significant economic losses to the shrimp farming industry. The glycolysis pathway plays an important role in the survival of EHP spores in vitro. In this study, key enzyme genes involved in the glycolysis pathway of EHP were analyzed, and purified spores were treated with KOH and a low temperature (−20 °C) to promote or inhibit germination. Quantitative analysis and enzyme activity of the initiating key gene hexokinase (HK) and the core link gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) were conducted to explore the energy response characteristics of germinating spores. The results showed that HK and GAPDH genes had significant differences from the host, based on phylogenetic analysis. The expression of HK gene and enzyme activity increased after promoting germination treatment. The expression of the GAPDH gene was stable, but the activity of the GAPDH enzyme increased significantly after germination promotion. These findings indicate that the inhibition of the HK gene expression level and GAPDH protein level can block spore germination and invasion in vitro, which could be used as potential control targets for EHP.

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Mining allergens in Cryptotympana atrata nymphs: integrating proteomics and homology-based bioinformatics - Yuan He; Shu-tao Sun; Jian-bo Xiao; Qi-dong Ren; Ying-ying Chen; Meng-qi Zhang; Mu-xuan Wang; Xu Guo; Jin-yue Sun; Chao Liu (Food Chemistry, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Liver-specific SLC13A3 modulation alleviates MASLD by regulating NAD+ metabolism - Jiangxia Du; Minhui Shen; Yuan Mu; Shuoran Peng; Zhifei Xu; Xiaochun Yang; Bo Yang; Peihua Luo; Hao Yan; Qiaojun He (Molecular and Cellular Biochemistry, 2026)

Effect of water temperature on the depletion of enrofloxacin and its metabolite ciprofloxacin in largemouth bass (Micropterus salmoides) tissue following repeated oral administrations - Ruiqi Fan; Xinyue Wang; Yuanyuan Ren; Shuang Li; Wenfei Guo; Jiaqi Liu; Yingchun Mu; Xiaoyu Wang; Sudong Xia; Bo Cheng (Aquaculture, 2026)

Impacts on the maximum lateral deflection and adjacent shield tunnels from the ground stiffness of an excavation - Fan-Yan Meng; Bo Hu; Mu-Chun Liu; Bin-Chen Benson Hsiung; Muhammad Dwiyanto Agung Prakasa (Tunnelling and Underground Space Technology, 2026)

Long-term remote sensing reveals the development of informal settlements and their impact on land surface temperature in African drylands: A case study of Windhoek, Namibia - Zilong Xia; Nan Jia; Bo Yuan; Ruishan Chen; Haowei Mu; Mo Bi; Uchendu Eugene Chigbu; Penghui Jiang (Sustainable Cities and Society, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Revealing the dynamic biological flow between eastern and western China from the perspective of ecological network - Haowei Mu; Shanchuan Guo; Kaixuan Pan; Bo Yuan; Zhou Fang; Xingang Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Structural diversity and properties of bio-based surfactants with their potential applications - Homely Isaya Mtui; Wei Wang; Shi-Zhong Yang; Bo-Zhong Mu (Bioresource Technology, 2026)

Bioconversion of CO2 to methane energy by Methanococcus maripaludis in newly-designed bioreactor system: Kinetic characteristics, parameter optimization and grid-quality production - Lei Zhou; Jie Gao; Le-Gang Chen; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Numerical simulation on creep behavior of argillaceous siltstone under compression-shear coupling and humidity variations - Jiajun Ran; Bo Hu; Qiaohai Tan; Xianghe Ye; Yugang Cheng; Zhiqiang Lv; Mostafa Sharifzadeh; Mi Nie; Jian Mu; Wenbin Guo (Ocean Engineering, 2025)

The predictability study of oceanic deep learning models: Taking Kuroshio intrusion into South China Sea as an example - Qiang Wang; Junkai Qian; Mu Mu; Peng Liang; Bo Qin (Ocean Modelling, 2025)

Physics-aware graph attention network for real-time water contamination forecasting - Feiyu Duan; Tianwei Mu; Bo Zhou; Baokuan Ning; Haoqiang Tan (Stochastic Environmental Research and Risk Assessment, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

Experimental research on drift of rescue targets in a basin under controllable wind-wave-current environment - Jiaqian Wang; Hao Qin; Haiwen Tu; Daosheng Wang; Zhengzhou Li; Bo Li; Hanxiang Su; Chuanfeng Liu; Lei Qin; Lin Mu (Ocean Engineering, 2025)

Microencapsulation of Acer truncatum seed oil using chickpea protein isolate–low/high-methoxy citrus pectin complex coacervates: Preparation, stability analysis, and application in milk - Mo Chen; Bo Zhang; Min Wang; Jin-yue Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Qi-dong Ren; Shu-tao Sun; Mohamed A. Farag; Xu Guo; Chao Liu (Food Hydrocolloids, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

The vital role of current-topography interaction and tidal mixing in the upwelling around Zhoushan Archipelago - Jianshe Mu; Juncheng Xie; Peng Bai; Bo Li; Jingling Yang; Ying Gao (Continental Shelf Research, 2025)

Assessment of Tropical Cyclone Disaster Damage Based on Learnable Inter-City Interaction GNN - Shijin Yuan; Laiyu Yang; Bin Mu; Bo Qin; Yanjun Huang (Journal of Meteorological Research, 2025)

An Interpretable NAO Daily Prediction Model Considering Weighted Causal Effects of Physical Processes - Shijin Yuan; Haoyu Wu; Bin Mu; Yuehan Cui; Bo Qin; Hao Li (Journal of Meteorological Research, 2025)

Mining robust in situ phosphorus-accumulating organisms via single-cell RACS-Culture for rational ecosystem engineering - Xiaoyan Jing; Yanhai Gong; Yishang Ren; Liyan Wang; Runzhi Mu; Pengcheng Sun; Zhidian Diao; Yu Meng; Liming Huang; Xixian Wang; Jia Zhang; Jiaxuan Luan; et al. (Water Research, 2025)

Corrigendum to “A novel indicator for assessing spatial coupling relationships within hybrid landscapes comprising diverse land cover types and its application to explaining urban thermal environment” [Sustainable Cities and Society 130 (2025) 106595] - Tao Mu; Ruting Zhao; Huawei Li; Yakai Lei; Qiuyuan Chen; Guohang Tian; Yali Zhang; Bo Mu (Sustainable Cities and Society, 2025)

Developing Intelligent Earth System Models : An AI scheme of K-profile parameterization and stable coupling into CESM with FTA - Bin Mu; Kang Yang; Bo Qin; Hao Li; Shijin Yuan (Ocean Modelling, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Enhancing methanogenesis from long-chain fatty acids (LCFA) and enrichment of novel bacteria with resuscitation-promoting factors - Bo Fang; Yi-Fan Liu; Hao-Xun Wei; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2025)

Dysregulated homocysteine metabolism and cardiovascular disease and clinical treatments - Xiangyu Cao; Tingyu Wang; Gaohang Mu; Yupeng Chen; Bo Xiang; Jingze Zhu; Zhenya Shen (Molecular and Cellular Biochemistry, 2025)

Hydrothermal alterations of the Ordovician carbonate reservoir rocks in the Ordos Basin - Nana Mu; Wenhui Huang; Bo Jiu; Baruch Spiro (Marine and Petroleum Geology, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Methane cycling in typical emerging proglacial lakes on the Tibetan Plateau: Insights into the metabolic mechanisms mediated by microorganisms - Meiqi Huang; Guangli Mu; Fuyuan Mai; Yanan Zhou; Xiaodong Li; Qing Yang; Bo Shao; Jiaqi Wang; Yindong Tong (Water Research, 2025)

A novel indicator for assessing spatial coupling relationships within hybrid landscapes comprising diverse land cover types and its application to explaining urban thermal environment - Tao Mu; Ruting Zhao; Huawei Li; Yakai Lei; Qiuyuan Chen; Guohang Tian; Yali Zhang; Bo Mu (Sustainable Cities and Society, 2025)

Triple microenvironment synergy engineering by grain boundaries of hydrophilic Cu electrode for boosting low-concentration nitrate electroreduction - Xin Wang; Qinian Wang; Mu Yuan; Xu Cheng; Bo Zhang; Ke Zhang; Lili Wang; Chao Wu; Xing Zhang (Chemical Engineering Journal, 2025)

EAAC-S2S: East Asian Atmospheric Circulation S2S Forecasting with a Deep Learning Model Considering Multi-Sphere Coupling - Bin Mu; Yuxuan Chen; Shijin Yuan; Bo Qin; Zhenchen Liu (Advances in Atmospheric Sciences, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

Integrating sequence and carbon isotope stratigraphy in the lower Cambrian (Stage 3), Tarim Basin: Implications for stratigraphic correlation and environmental-biotic evolution - Bo Yang; Daizhao Chen; Mu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Maintaining shallow waters to maximize the potential of saltpans as foraging habitat for migratory shorebirds along an endangered flyway - Weipan Lei; José A. Masero; Ziwen Chai; Bing-Run Zhu; Tong Mu; He-Bo Peng; Zhengwang Zhang; Theunis Piersma (Biological Conservation, 2025)

Evolution Mechanism of Water-Conducting Channels and Disaster Triggering Induced by Fault Zone Failure in a Mining Roadway - Jian Chen; Lianchong Li; Wenqiang Mu; Xin Wang; Bo Ren (Mine Water and the Environment, 2025)

A new control strategy of sulfate-reducing microorganisms and corrosion rate from a high-temperature oil reservoir by nitrate/nitrite coupling with nitrate-reducing bacteria - Lei Zhou; Jie Gao; Yu-Xuan Li; Jun Wu; Biao Wang; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

High-entropy (FeMnMoNi)Se2 nanoflower structure with multi-active sites for urea-assisted hydrogen generation - Yumo Fu; Hao Liu; Bo Gao; Jianjia Mu; Guoqing Guan; Zhongbao Feng (Chemical Engineering Journal, 2025)

Quantifying the anthropogenic sensitivity of ecological patterns in arid urban agglomeration - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Chunqiang Li; Peijun Du (Applied Geography, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

A fusion of oncolytic viruses and bispecific T-cell engagers for triple negative breast cancer immunotherapy - Min Mu; Hui Li; Guoqing Wang; Bo Chen; Rangrang Fan; Nianyong Chen; Bingwen Zou; Aiping Tong; Gang Guo (Chemical Engineering Journal, 2025)

Ultralow nano-hierarchical filler loadings enhance the energy storage performance of PEI-based nanocomposites - Zijun Mu; Jin Qian; Guanglong Ge; Simin Wang; Hairui Bai; Guohui Li; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2025)

Evaluation of the buffer-blocking capacity of acrocarpous moss Campylopus schmidii as candidate for copper and cadmium migration - Rong Zhang; Feiyun Huang; Zhuang Ju; Bo Mu; Peng Chen (Environmental Research, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Moving in the landscape: Omnidirectional connectivity dynamics in China from 1985 to 2020 - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Zilong Xia; Pengfei Tang; Wei Zhang; Peng Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2025)

Scalable, flexible and hierarchically porous Janus membrane inducing Zn-Ion flux redistribution and desolvation for dendrite-free zinc anodes - Jiawei Mu; Miao Yu; Bo Zhao; Yan Dai; Tiantian Li; Xiangcun Li; Xinhong Qi; Xuri Wang; Gaohong He (Chemical Engineering Journal, 2025)

Predictability Study of Weather and Climate Events Related to Artificial Intelligence Models - Mu Mu; Bo Qin; Guokun Dai (Advances in Atmospheric Sciences, 2025)

Sparse large trees in secondary and planted forests highlight the need to improve forest conservation and management - Chao Jin; Jiejie Jiao; Chuping Wu; Yumei Mu; Shilu Zheng; Lijia You; Wanben Wu; Jinliang Liu; Bo Jiang (Science of The Total Environment, 2024)

An extension to ensemble forecast of conditional nonlinear optimal perturbation considering nonlinear interaction between initial and model parametric uncertainties - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Xing-Rong Chen; Bo Qin; Guo-Kun Dai (Atmospheric Research, 2024)

A deep learning-based global tropical cyclogenesis prediction model and its interpretability analysis - Bin Mu; Xin Wang; Shijin Yuan; Yuxuan Chen; Guansong Wang; Bo Qin; Guanbo Zhou (Science China Earth Sciences, 2024)

Quantifying the drought sensitivity of vegetation types in northern China from 1982 to 2022 - Bo Yuan; Shanchuan Guo; Xingang Zhang; Haowei Mu; Shengpeng Cao; Zilong Xia; Xiaoquan Pan; Peijun Du (Agricultural and Forest Meteorology, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Improvement of model simulation for summer PM2.5 and O3 through coupling with two new potential HONO sources in the North China Plain - Xiaoxi Zhao; Min Song; Xiujuan Zhao; Chaoyang Xue; Pengfei Liu; Can Ye; Xiaowei He; Yujing Mu; Bo Hu (Science of The Total Environment, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

A synergetic binary system of waste cooking oil-derived bio-based surfactants and its interfacial performance for enhanced oil recovery - Ming-Yue Liang; Chi Ma; Wan-Qi Qin; Homely Isaya Mtui; Wei Wang; Jin-feng Liu; Shi-Zhong Yang; Bo-Zhong Mu (Colloids and Surfaces C: Environmental Aspects, 2024)

Recent progress on interface characterization methods of carbon fiber reinforced polymer composites - Xiaomin Yuan; Zhihua Zhang; Xuanyu Mu; Chuan Shan; Xueping Gao; Bo Zhu (Chemical Engineering Journal, 2024)

Seasonal simulation and source apportionment of SO42− with integration of major highlighted chemical pathways in WRF-Chem model in the NCP - Xiaoxi Zhao; Xiujuan Zhao; Dan Chen; Jing Xu; Yujing Mu; Bo Hu (Atmospheric Pollution Research, 2024)

Research on Influencing Factors of Cable Clamp Bolt Elastic Interaction in Cross-Ocean Suspension Bridges - Fengrui Mu; Bo Wang; Yongjun Zhou; Yuan Jing; Yu Zhao; Zhiran Luo (Journal of Marine Science and Engineering, 2024)
Suspension bridges are the most common type of bridge used to cross the ocean. The cable clamps in suspension bridges clamp the main cables by bolt preload, but the elastic interaction of the bolts reduces the preload, which is detrimental to the force in suspension bridges. However, research on the factors influencing the elastic interaction of cable clamp bolts in suspension bridges is currently limited. This paper aims to explore the law of influence of external factors on the elastic interaction of bolts through a combined approach of theoretical analysis, full-scale experiment, and finite element simulation. The results indicate that the average preload loss was reduced by about 27% when the elastic modulus was increased by about 110%. The average preload loss was reduced by about 45% when the bolt center distance was increased by 75%. The number of bolts has a small effect on the elastic interaction, which can be ignored. When the preload of bolt installation was increased by 133%, the average preload loss was reduced by approximately 125%, which was almost a linear relationship. Tightening the bolt from the center bolt creates greater elastic interaction. The conclusions can provide suggestions for reducing the elastic interaction of bolts in the design and construction of suspension bridge cable clamps.

A culture-dependent analysis of anaerobic methylotrophs in oil reservoir systems - Lin-Yuan Huang; Yi-Fan Liu; Wan-Qi Qin; Shi-Yi Wang; Yuan-Hao Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

The regulation effect of urban green space on air particulate matter concentration under different matrices in Xi'an city - Bo Jiang; Shiyu Fan; Chang Sun; Sen Mu; Tian Gao; Ling Qiu (Air Quality, Atmosphere & Health, 2024)

Middle Ordovician climatic and oceanic destabilization in a slope-setting of the Yangtze platform, South China, and its role as a regional brake on the Ordovician radiations - Chaogang Fang; Mu Liu; Chengcheng Zhang; Hailei Tang; Jianqing Li; Guangfu Xing; Fengjie Li; Naicen Xu; Tong Wu; Bo Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

An Experimental Study on Fracturing Response and Slurry Flow of High-Pressure Grouting in Fractured Rock - Wenqiang Mu; Lianchong Li; Honglei Liu; Bo Ren; Jian Chen; Xin Wang (Rock Mechanics and Rock Engineering, 2024)

Multivariate Upstream Kuroshio Transport (UKT) Prediction and Targeted Observation Sensitive Area Identification of UKT Seasonal Reduction - Bin Mu; Yifan Yang-Hu; Bo Qin; Shijin Yuan (Ocean Modelling, 2024)

Developing intelligent Earth System Models: An AI framework for replacing sub-modules based on incremental learning and its application - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Bo Qin; Guo-Kun Dai; Guan-Bo Zhou (Atmospheric Research, 2024)

Responses and resistance capacity of Solanum nigrum L. mediated by three ecological category earthworms in metal-[Cd-As-Cu-Pb]-contaminated soils of North China - Xiaoquan Mu; Bo Li; Wenju Liu; Yuhui Qiao; Caide Huang; Yang Yang; Menghan Zhang; Xinru Wang; Yanan Liu; Yue Yin; Kun Wang (Science of The Total Environment, 2024)

Utilizing soil organic phosphorus for sustainable crop production: insights into the rhizosphere - Kai Zhang; Dongfang Zheng; Yu Gu; Jie Xu; Maoying Wang; Bo Mu; Sijie Wen; Tao Tang; Zed Rengel; Jianbo Shen (Plant and Soil, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Development and application of greenhouse light environment simulation technology based on light path tracing - Zhihui Mu; Yu Bo; Jihang Xu; Kai Song; Boda Dong; Jian Wang; Sheng Shu; Yu Wang; Shirong Guo (Computers and Electronics in Agriculture, 2024)

A bibliometric assessment of the science and practice of blue–green space (BGS): hot spots, lacunae, and opportunities - Bo Mu; Ruting Zhao; Yang Liu; Enkai Xu; Yali Zhang; Hong Wei; Guohang Tian (Socio-Ecological Practice Research, 2024)

Variation of runoff-sediment relationship at flood event scale in three typical watersheds of the Loess Plateau - Ren Geng; Zixuan Ye; Peng Tian; Qiu Jin; Bo Bi; Guangju Zhao; Xingmin Mu; Tongshun Wang; Dadong Zhu (CATENA, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Importance of habitat heterogeneity in tidal flats to the conservation of migratory shorebirds - Shangxiao Cai; Tong Mu; He‐Bo Peng; Zhijun Ma; David S. Wilcove (Conservation Biology, 2024)
Understanding species distribution patterns and what determines them is critical for effective conservation planning and management. In the case of shorebirds migrating along the East Asian‐Australasian Flyway (EAAF), the loss of stopover habitat in the Yellow Sea region is thought to be the primary reason for the precipitous population declines. However, the rates of decline vary considerably among species, and it remains unclear how such differences could arise within a group of closely related species using apparently similar habitats at the same locales. We mapped the spatial distributions of foraging shorebirds, as well as biotic (benthic invertebrates consumed by migrating shorebirds) and abiotic (sediment characteristics) environmental factors, at a key stopover site in eastern China. Five of the six sediment characteristics showed significant spatial variation with respect to distance along the shoreline or distance from the seawall in the same tidal flat. The biomasses of four of the six most abundant benthic invertebrates were concentrated in the upper or middle zones of the tidal flat. The distribution patterns of all three focal shorebird species on the tidal flat were best explained jointly by this heterogeneity of sediment characteristics and invertebrate prey. These results suggest that the loss of tidal flats along the Yellow Sea, which is typically concentrated at the upper and middle zones, may not only reduce the overall amount of staging habitat, but also disproportionately affect the most resource‐rich portions for the birds. Effective conservation of shorebird staging areas along the EAAF and likely elsewhere must consider the subtle habitat heterogeneity that characterizes these tidal flats, prioritizing the protection of those portions richest in food resources, most frequently used by focal bird species, and most vulnerable to anthropogenic threats. Article impact statement : Heterogeneity of tidal flats with respect to biotic and abiotic factors must be considered in shorebird conservation planning.

Effect of induction mode on 3D printing characteristics of whey protein isolate emulsion gel - Guohua Li; Bo Wang; Weiqiao Lv; Rongyi Mu; Yuanliang Zhong (Food Hydrocolloids, 2024)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

Modeling of farmers’ production performance portrait based on GASA-WFCM clustering - Bo Wang; Yan Shi; Weisong Mu; Jianying Feng (Computers and Electronics in Agriculture, 2023)

pH-dependent bisphenol A transformation and iodine disinfection byproduct generation by peracetic acid: Kinetic and mechanistic explorations - Shurun Yang; Yongli He; Zhechao Hua; Zhihui Xie; Chuan-Shu He; Zhaokun Xiong; Ye Du; Yang Liu; Guowei Xing; Jingyun Fang; Yang Mu; Bo Lai (Water Research, 2023)

Highly sensitive detection of microRNA-21 by nitrogen-doped carbon dots-based ratio fluorescent probe via nuclease-assisted rolling circle amplification strategy - Shan Huang; Bo Li; Pingping Mu; Wenqian Zhang; Yi Liu; Qi Xiao (Analytica Chimica Acta, 2023)

A paralleled embedding high-dimensional Bayesian optimization with additive Gaussian kernels for solving CNOP - Shijin Yuan; Yaxuan Liu; Bo Qin; Bin Mu; Kun Zhang (Ocean Modelling, 2023)

Effect of hexavalent chromium exposure on the reproductive status and biomarker responses of female Geloina erosa - Hongling Mu; Gongsi Wang; Bo Huang; Xiangchao Fu; Sui Cheng; Jiao Wen (Ecotoxicology, 2023)

Eugenilones A−N: sesquiterpenoids from the fruits of Eugenia uniflora - Mu Chen; Run-Qiang Chen; Yuan Guo; Jian-Xin Chen; Qian Jin; Mei-Hong Chen; Bo-Yong Chen; Zheng-Chao Tu; Wen-Cai Ye; Lei Wang (Phytochemistry, 2023)

Sesquiterpenoids from the fruits of Alpinia oxyphylla Miq. and their neuroprotective effect - Chengxing Qiu; Liping Mu; Ji Wang; Ran Tang; Bo Hou; Weiyan Hu; Rongping Zhang; Xinglong Chen (Phytochemistry, 2023)

Novel biological nitrogen removal process for the treatment of wastewater with low carbon to nitrogen ratio: A review - Kaiyao Hu; Wenxuan Li; Yaning Wang; Bo Wang; Hao Mu; Shuang Ren; Kexin Zeng; Hongjuan Zhu; Jinming Liang; Ya'e Wang; Juqiang Xiao (Journal of Water Process Engineering, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Embelin protects against apoptosis and inflammation by regulating PI3K/Akt signaling in IL-1β-stimulated human nucleus pulposus cells - Xiaoliang Bai; Jie Wang; Siguang Ding; Shuai Yang; Bo Pei; Mingyan Yao; Xiaojuan Zhu; Meichao Jiang; Mingyuan Zhang; Weina Mu; Shuqin Guo (Tissue and Cell, 2023)

In-situ anaerobic treatment removes the passivation layer of sponge iron to restore the nitrogen and phosphorus removal performance of SBR - Kaiyao Hu; Wenxuan Li; Hao Mu; Shuang Ren; Hongjuan Zhu; Kexin Zeng; Bo Wang; Jinming Liang; Qi Zhang; Lili Yang; Wei Zhao; Juqiang Xiao (Process Safety and Environmental Protection, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

Association between urinary cadmium level and subclinical myocardial injury in the general population without cardiovascular disease aged ≥ 50 years - Yu-Jie Wu; Si-Bo Wang; Jia-Teng Sun; Ling-Feng Gu; Ze-Mu Wang; Bo Deng; Hao Wang; Lian-Sheng Wang (Environmental Science and Pollution Research, 2023)

Investigating the resistance responses to Alternaria brassicicola in 'Korla' fragrant pear fruit induced by a biocontrol strain Bacillus subtilis Y2 - Xiaojie Wang; Siyu Xie; Xiangyi Mu; Bo Guan; Youzhen Hu; Yongqing Ni (Postharvest Biology and Technology, 2023)

Error Evolutions and Analyses on Joint Effects of SST and SL via Intermediate Coupled Models and Conditional Nonlinear Optimal Perturbation Method - Bin Mu; Xiaoyun Qin; Shijin Yuan; Bo Qin (Journal of Marine Science and Engineering, 2023)
A seasonal predictability barrier has long been noticed in ENSO forecasting with numerical models. Previous studies explored the impact of seasonal optimal initial perturbation evolutions in sea surface temperature anomalies (SSTA) on ENSO forecasting using the intermediate coupled model (ICM) via the conditional nonlinear optimal perturbation (CNOP) method. In this paper, we investigate the joint effects of SSTA and sea level anomalies (SLA) from the perspective of the optimal growth initial error (OGE). After determining the four seasonal OGEs about SSTA and SLA (i.e., SSTA-OGE, SLA-OGE and Joint-OGE), we first demonstrate the patterns, evolutions and the resulting spring predictability barrier (SPB) of the above OGEs. Then, we analyze the mechanism of OGE evolutions and SPB. Finally, we conduct observing system simulation experiments to determine the best (economic) observation network. Our experimental results indicate that the ENSO evolution error induced by SSTA-OGE and Joint-OGE presents season dependency, but SLA-OGE has no impact on ENSO evolution. Moreover, Joint-OGEs induce error evolutions and the SPB with more significant intensity than SSTA-OGEs and SLA-OGEs. From mechanism analyses, the evolutions of SSTA-OGEs are mainly dominated by Bjerknes feedback. Further, the evolution dynamics of Joint-OGEs primarily contain the continuous heating between the upper ocean combined with Bjerknes feedback and thermal diffusion in response to the discharge process. In addition, comprehensive and economical sensitive areas are identified through Joint-OGE, including the central-eastern equatorial Pacific and the western and north-eastern tropical Pacific boundary, which contribute to the ENSO prediction benefits reaching 58.31% on average.

Failure Mechanism of Grouted Floor with Confined Aquifer Based on Mining-Induced Data - Wenqiang Mu; Lianchong Li; Yongshu Zhang; Guofeng Yu; Bo Ren (Rock Mechanics and Rock Engineering, 2023)

Basal Forebrain Cholinergic Innervation Induces Depression-Like Behaviors Through Ventral Subiculum Hyperactivation - Nana Yu; Huina Song; Guangpin Chu; Xu Zhan; Bo Liu; Yangling Mu; Jian-Zhi Wang; Yisheng Lu (Neuroscience Bulletin, 2023)
Malfunction of the ventral subiculum (vSub), the main subregion controlling the output connections from the hippocampus, is associated with major depressive disorder (MDD). Although the vSub receives cholinergic innervation from the medial septum and diagonal band of Broca (MSDB), whether and how the MSDB-to-vSub cholinergic circuit is involved in MDD is elusive. Here, we found that chronic unpredictable mild stress (CUMS) induced depression-like behaviors with hyperactivation of vSub neurons, measured by c-fos staining and whole-cell patch-clamp recording. By retrograde and anterograde tracing, we confirmed the dense MSDB cholinergic innervation of the vSub. In addition, transient restraint stress in CUMS increased the level of ACh in the vSub. Furthermore, chemogenetic stimulation of this MSDB-vSub innervation in ChAT - Cre mice induced hyperactivation of vSub pyramidal neurons along with depression-like behaviors; and local infusion of atropine, a muscarinic receptor antagonist, into the vSub attenuated the depression-like behaviors induced by chemogenetic stimulation of this pathway and CUMS. Together, these findings suggest that activating the MSDB-vSub cholinergic pathway induces hyperactivation of vSub pyramidal neurons and depression-like behaviors, revealing a novel circuit underlying vSub pyramidal neuronal hyperactivation and its associated depression.

Effect of CDM3 on co-culture of human-induced pluripotent stem cells with Matrigel-covered polycaprolactone to prepare cardiac patches - Yue Dai; Fan Zhou; Jianwei Zheng; Junsheng Mu; Ping Bo; Bin You (In Vitro Cellular & Developmental Biology - Animal, 2023)

Bidirectional reflectance factor measurement of conifer needles with microscopic spectroscopy imaging - Yongkang Lai; Xihan Mu; Yuequn Bian; Xiaohan Dong; Feng Qiu; Xinyu Bo; Zhixiang Zhang; Yi Li; Xinli Liu; Linyuan Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2023)

Characteristics of microbiota, core sulfate-reducing taxa and corrosion rates in production water from five petroleum reservoirs in China - Lei Zhou; Jun Wu; Jia-Heng Ji; Jie Gao; Yi-Fan Liu; Biao Wang; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Science of The Total Environment, 2023)

Distribution of Li, Ga, Nb, and REEs in coal as determined by LA-ICP-MS imaging: A case study from Jungar coalfield, Ordos Basin, China - Bo Jiu; Wenhui Huang; Baruch Spiro; Ruilin Hao; Nana Mu; Long Wen; Huidi Hao (International Journal of Coal Geology, 2023)

Improvement of extrudability and self-support of emulsion-filled starch gel for 3D printing: Increasing oil content - Rongyi Mu; Bo Wang; Weiqiao Lv; Jie Yu; Guohua Li (Carbohydrate Polymers, 2023)

dmrt3, nom1, abce1, and pkmyt1 play key roles in gonadal sex determination in Acrossocheilus fasciatus - Yuting Ren; Yi Mu; Bo Zhao; Yang Gao; Xiaoxin Dai; Zhangjie Chu (Aquaculture International, 2023)

Validation and accuracy analysis of wind products from scatterometer onboard the HY-2B satellite - Sheng Yang; Bo Mu; Haoqiang Shi; Chaofei Ma; Wu Zhou; Juhong Zou; Mingsen Lin (Acta Oceanologica Sinica, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Investigation of a Method to Prevent Rock Failure and Disaster Due to a Collapse Column Below the Mine - Bo Ren; Liang Yuan; Wenqiang Mu; Yongshu Zhang; Guofeng Yu; Chengping Cao; Minhua Wang; Yong Luo; Lianchong Li (Mine Water and the Environment, 2022)

A Variational Bayesian-Based Simultaneous Localization and Mapping Method for Autonomous Underwater Vehicle Navigation - Pengcheng Mu; Xin Zhang; Ping Qin; Bo He (Journal of Marine Science and Engineering, 2022)
Simultaneous Localization and Mapping (SLAM) is a well-known solution for mapping and realizing autonomous navigation of an Autonomous Underwater Vehicle (AUV) in unknown underwater environments. However, the inaccurate time-varying observation noise will cause filtering divergence and reduce the accuracy of localization and feature estimation. In this paper, VB-AUFastSLAM based on the unscented-FastSLAM (UFastSLAM) and the Variational Bayesian (VB) is proposed. The UFastSLAM combines unscented particle filter (UPF) and unscented Kalman filter (UKF) to estimate the AUV poses and features. In addition, to resist the unknown time-varying observation noise, the method of Variational Bayesian learning is introduced into the SLAM framework. Firstly, the VB method is used to estimate the joint posterior probability of the AUV path and observation noise. The Inverse-Gamma distribution is used to model the observation noise and real-time noise parameters estimation is performed to improve the AUV localization accuracy. Secondly, VB is reused to estimate the noise parameters in the feature update stage to enhance the performance of the feature estimation. The proposed algorithms are first validated in an open-source simulation environment. Then, an AUV SLAM system based on the Inertial Navigation System (INS), Doppler Velocity Log (DVL), and single-beam Sonar are also built to verify the effectiveness of the proposed algorithms in the marine environment. The accuracy of the proposed methods can reach 0.742% and 0.776% of the range, respectively, which is much better than 1.825% and 1.397% of the traditional methods.

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Distribution patterns of the earthworm community in relation to soil properties and metals in agro-ecosystems in Hebei Province, North China - Yue Yin; Dianwu Wang; Miaomiao Chen; Xiaoquan Mu; Yang Yang; Bo Li; Kun Wang (Community Ecology, 2022)

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Xiaoxin Dai; Lijun Qiu; Han Zhang; Chunying Xu; Bo Zhao; Yang Gao; Haidong Li; Yi Mu; Zhangjie Chu (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization, and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes were significantly decreased in the bisphenol A-exposed group, while the co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed, and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affects the mitochondrial respiratory chain in ovaries and may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols play a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Native herbivores indirectly facilitate the growth of invasive Spartina in a eutrophic saltmarsh - Xiao Xu; Yan Zhang; Songshuo Li; Hongyang Chen; Mu Liu; Bo Li; Ming Nie (Ecology, 2022)
Current theory (e.g., consumer‐controlled theory) predicts that nutrient enrichment typically amplifies herbivory and thereby suppresses the growth and expansion of invasive plants. Herbivores can facilitate plant regrowth in the native community by stimulating complementary growth or ameliorating habitat conditions (e.g., by increasing soil oxygen and nutrient availability), but whether they have similar positive effects on invasive plants, especially under nutrient enrichment, remains unknown. Using a field nitrogen (N)‐enrichment × crab exclusion experiment, we evaluated and compared the effects of both N enrichment and crab herbivory on the growth performance of a global invasive cordgrass, Spartina alterniflora , and a co‐occurring native plant, Phragmites australis . We found that crabs consistently suppressed P. australis by density and aboveground biomass regardless of N enrichment. In contrast, for S. alterniflora , the negative effects of crabs under ambient N were replaced by positive effects under N enrichment, with crabs stimulating complementary increases in density and aboveground biomass. The differing effects between the N treatments were driven by crab burrowing activity, which increased soil N availability, and the nutrient‐use efficiency of S. alterniflora . Our findings revealed that native herbivores can have opposing effects on native and invasive plants, which broadens our understanding of how exotic plants can achieve dominance in a changing world.

Plant invasion alters latitudinal pattern of plant‐defense syndromes - Mu Liu; Yuanfei Pan; Xiaoyun Pan; Alejandro Sosa; Dana M. Blumenthal; Mark Van Kleunen; Bo Li (Ecology, 2021)
The relationship between herbivory and latitude may differ between native and introduced populations of invasive plants, which can generate latitudinal heterogeneity in the strength of enemy release. However, still little is known about how latitudinal heterogeneity in herbivore pressure influences latitudinal variation in defense phenotypes of invasive plants. We tested how latitudinal patterns in multi‐variate defense syndromes differed between native (Argentinian) and introduced (Chinese) populations of the invasive herb Alternanthera philoxeroides . In addition, to better understand the drivers underlying latitudinal patterns, we also tested whether associations of defense syndromes with climate and herbivory differed between native and introduced ranges. We found that native plant populations clustered into three main defense syndromes associated with latitude. In contrast, we only found two defense syndromes in the introduced range. One matched the high‐latitude syndrome from the native range, but was distributed at both the northern and southern range limits in the introduced range. The other was unique to the introduced range and occurred at mid‐latitudes. Climatic conditions were associated with variation in syndromes in the native range, and climatic conditions and herbivory were associated with variation in syndromes in the introduced range. Together, our results demonstrate that plants may under the new environmental conditions in the introduced range show latitudinal patterns of defense syndromes that are different from those in their native range. This emphasizes that geographical dependence of population differentiation should be explicitly considered in studies on the evolution of defense in invasive plants.

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Coupling relationship between construction land expansion and PM2.5 in China - Liang Zhou; Bo Yuan; Haowei Mu; Xuewei Dang; Shaohua Wang (Environmental Science and Pollution Research, 2021)

Preliminary calibration results of the HY-2B altimeter’s SSH at China’s Wanshan calibration site - Chuntao Chen; Jianhua Zhu; Chaofei Ma; Mingsen Lin; Longhao Yan; Xiaoqi Huang; Wanlin Zhai; Bo Mu; Yongjun Jia (Acta Oceanologica Sinica, 2021)

Sea level anomaly intelligent inversion model based on LSTM-RBF network - Hanmin Liu; Bo He; Ping Qin; Xin Zhang; Shuai Guo; Xiaokai Mu (Meteorology and Atmospheric Physics, 2021)

The gut bacterial flora associated with brown planthopper is affected by host rice varieties - Zheng-Liang Wang; Hai-bo Pan; Wei Wu; Mu-Yu Li; Xiao-Ping Yu (Archives of Microbiology, 2021)

Quantitative Determination of Trace Lipopeptide Using HPLC through Double Carboxyls Labelling - Shi-Zhong Yang; Hong-Zhi Quan; Jin-Feng Liu; Hong-Ze Gang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2020)

Safety of azithromycin in pediatrics: a systematic review and meta-analysis - Linan Zeng; Peipei Xu; Imti Choonara; Zhenyan Bo; Xiangchen Pan; Wenyan Li; Xiaofeng Ni; Tao Xiong; Can Chen; Leshan Huang; Shamim Ahmad Qazi; Dezhi Mu; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromycin and placebo or other antibiotics using meta-analysis of RCTs. Results We included 133 studies with 4243 ADRs reported in 197,675 neonates, infants, and children who received azithromycin. The safety of azithromycin as MDA in pediatrics was poorly monitored. The main ADRs were diarrhea and vomiting. In prospective non-MDA studies, the most common toxicity was gastrointestinal ADRs (938/1967; 47.7%). The most serious toxicities were cardiac (prolonged QT or irregular heart beat) and idiopathic hypertrophic pyloric stenosis (IHPS). Compared with placebo, azithromycin did not show increased risk ADRs based on RCTs (risk difference − 0.17 to 0.07). The incidence of QT prolonged was higher in the medium-dosage group (10–30 mg/kg/day) than that of low-dosage group (≤ 10 mg/kg/day) (82.0% vs 1.2%). Conclusion The safety of azithromycin as MDA needs further evaluation. The most common ADRs are diarrhea and vomiting. The risk of the most serious uncommon ADRs (cardiac-prolonged QT and IHPS) is unknown.

Sources of particulate organic matter in the Chukchi and Siberian shelves: clues from carbon and nitrogen isotopes - Renming Jia; Xinyue Mu; Min Chen; Jing Zhu; Bo Wang; Xiaopeng Li; A. S. Astakhov; Minfang Zheng; Yusheng Qiu (Acta Oceanologica Sinica, 2020)

Genome‐wide comparison of Carnobacterium maltaromaticum derived from diseased fish harbouring important virulence‐related genes - HyeongJin Roh; Bo Seong Kim; Mu Kun Lee; Chan‐Il Park; Do‐Hyung Kim (Journal of Fish Diseases, 2020)
Although Carnobacterium maltaromaticum has been used as a probiotic in fish, it was reported to cause disease for the first time in Korea. The objective of this study was to understand the differences between pathogenic and non‐pathogenic strains. Pathogenicity was tested by challenging rainbow trout with C. maltaromaticum ATCC35586 and 18ISCm isolated from diseased fish, and DSM20342 isolated from a dairy product. We also compared 24 genomes of C. maltaromaticum strains plus the genome of our isolate 18ISCm sequenced in this study. Only the strains from diseased fish caused high mortality with severe histopathological changes. Although all strains shared more than 90% of Ko_id, wecC and xtmA were found only in strains from diseased fish. Interestingly, only strains from diseased fish harboured two wecC paralogs involved in the production of D‐mannosaminuronic acid which is a major component of a well‐known virulence factor, teichuronic acid. Two wecC paralogs of 18ISCm were increased when they were co‐cultured with trout blood cells, suggesting that wecC genes might play a role in virulence. The results of this study show that strains isolated from diseased fish are different from strains derived from food in terms of pathogenicity to fish and the presence of virulence‐related genes.

Testing the shifting defense hypothesis for constitutive and induced resistance and tolerance - Mu Liu; Xiaoyun Pan; Zhijie Zhang; Mark van Kleunen; Bo Li (Journal of Pest Science, 2020)

Development of Land Surface Model BCC_AVIM2.0 and Its Preliminary Performance in LS3MIP/CMIP6 - Weiping Li; Yanwu Zhang; Xueli Shi; Wenyan Zhou; Anning Huang; Mingquan Mu; Bo Qiu; Jinjun Ji (Journal of Meteorological Research, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Permian integrative stratigraphy and timescale of China - Shuzhong Shen; Hua Zhang; Yichun Zhang; Dongxun Yuan; Bo Chen; Weihong He; Lin Mu; Wei Lin; Wenqian Wang; Jun Chen; Qiong Wu; Changqun Cao; et al. (Science China Earth Sciences, 2019)

Coralloluteibacterium thermophilus sp. nov., A Gammaproteobacterium Isolated from an Oil Reservoir - Jing You; Shan Hong; Jiliang Yu; Lisha Duan; Bo Liu; Bozhong Mu; Cheng Zhou; Yanfen Xue (Current Microbiology, 2018)

First report of nocardia infection in cultured Japanese eel, Anguilla japonica - Bo Seong Kim; Ji Won Park; Gyoung Sik Kang; Ji Hye Jin; Heyong Jin Roh; Do Hyung Kim; Mu Kun Lee; Min Do Huh (Journal of Fish Diseases, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Anaerobic biodegradation of partially hydrolyzed polyacrylamide in long-term methanogenic enrichment cultures from production water of oil reservoirs - Hao Hu; Jin-Feng Liu; Cai-Yun Li; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Biodegradation, 2018)

Characteristics of thawed interlayer and its effect on embankment settlement along the Qinghai-Tibet Railway in permafrost regions - Zhi-zhong Sun; Wei Ma; Shu-juan Zhang; Yan-hu Mu; Han-bo Yun; Hong-lei Wang (Journal of Mountain Science, 2018)

Contrasting effects of specialist and generalist herbivores on resistance evolution in invasive plants - Zhijie Zhang; Xiaoyun Pan; Dana Blumenthal; Mark van Kleunen; Mu Liu; Bo Li (Ecology, 2018)
Invasive alien plants are likely to be released from specialist herbivores and at the same time encounter biotic resistance from resident generalist herbivores in their new ranges. The Shifting Defense hypothesis predicts that this will result in evolution of decreased defense against specialist herbivores and increased defense against generalist herbivores. To test this, we performed a comprehensive meta‐analysis of 61 common garden studies that provide data on resistance and/or tolerance for both introduced and native populations of 32 invasive plant species. We demonstrate that introduced populations, relative to native populations, decreased their resistance against specialists, and increased their resistance against generalists. These differences were significant when resistance was measured in terms of damage caused by the herbivore, but not in terms of performance of the herbivore. Furthermore, we found the first evidence that the magnitude of resistance differences between introduced and native populations depended significantly on herbivore origin (i.e., whether the test herbivore was collected from the native or non‐native range of the invasive plant). Finally, tolerance to generalists was found to be higher in introduced populations, while neither tolerance to specialists nor that to simulated herbivory differed between introduced and native plant populations. We conclude that enemy release from specialist herbivores and biotic resistance from generalist herbivores have contrasting effects on resistance evolution in invasive plants. Our results thus provide strong support for the Shifting Defense hypothesis.

Characterization of bacterial composition and diversity in a long-term petroleum contaminated soil and isolation of high-efficiency alkane-degrading strains using an improved medium - Jun Zheng; Jun-Qiao Feng; Lei Zhou; Serge Maurice Mbadinga; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2018)

Propionate metabolism and diversity of relevant functional genes by in silico analysis and detection in subsurface petroleum reservoirs - Tao Yang; Serge Maurice Mbadinga; Lei Zhou; Shi-Zhong Yang; Jing-Feng Liu; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Identification of potential cargo proteins of transportin protein AtTRN1 in Arabidopsis thaliana - Bo Yan; Xiaoning Wang; Zhenyu Wang; Ni Chen; Changjun Mu; Kaili Mao; Lirong Han; Wei Zhang; Heng Liu (Plant Cell Reports, 2016)

Reduction of acrylamide level through blanching with treatment by an extremely thermostable l-asparaginase during French fries processing - Shaohua Zuo; Tao Zhang; Bo Jiang; Wanmeng Mu (Extremophiles, 2015)

Proteomics analysis for enhanced lipid accumulation in oleaginous Chlorella vulgaris under a heterotrophic-Na+ induction two-step regime - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han; Bo Feng; Hongyan Zeng (Biotechnology Letters, 2015)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

Structural characterization of rhamnolipid produced by Pseudonomas aeruginosa strain FIN2 isolated from oil reservoir water - Jin-Feng Liu; Gang Wu; Shi-Zhong Yang; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2014)

Enzymatic production of d-3-phenyllactic acid by Pediococcus pentosaceus d-lactate dehydrogenase with NADH regeneration by Ogataea parapolymorpha formate dehydrogenase - Shuhuai Yu; Lanjun Zhu; Chen Zhou; Tao An; Bo Jiang; Wanmeng Mu (Biotechnology Letters, 2014)

Characterization of a d-psicose-producing enzyme, d-psicose 3-epimerase, from Clostridium sp. - Wanmeng Mu; Wenli Zhang; Dan Fang; Leon Zhou; Bo Jiang; Tao Zhang (Biotechnology Letters, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Characterization of ribose-5-phosphate isomerase converting d-psicose to d-allose from Thermotoga lettingae TMO - Zaiping Feng; Wanmeng Mu; Bo Jiang (Biotechnology Letters, 2013)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

Matrix metalloproteinase 2 overexpression and prognosis in colorectal cancer: a meta-analysis - Mumu Shi; Bo Yu; Hongguo Gao; Jingwen Mu; Changwei Ji (Molecular Biology Reports, 2013)

Analyses of n-alkanes degrading community dynamics of a high-temperature methanogenic consortium enriched from production water of a petroleum reservoir by a combination of molecular techniques - Lei Zhou; Kai-Ping Li; Serge Maurice Mbadinga; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Ecotoxicology, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Characterization of d-lactate dehydrogenase from Pediococcus acidilactici that converts phenylpyruvic acid into phenyllactic acid - Wanmeng Mu; Shuhuai Yu; Bo Jiang; Xingfeng Li (Biotechnology Letters, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

The application of sea-surface wind detection with doppler lidar in Olympic sailing - Gaili Wang; Liping Liu; Zhishen Liu; Bo Lü; Rong Mu (Advances in Atmospheric Sciences, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Characterization of d-tagatose-3-epimerase from Rhodobacter sphaeroides that converts d-fructose into d-psicose - Longtao Zhang; Wanmeng Mu; Bo Jiang; Tao Zhang (Biotechnology Letters, 2009)

Variants of Lipopeptides Produced by Bacillus licheniformis HSN221 in Different Medium Components Evaluated by a Rapid Method ESI-MS - Yi-Ming Li; Namir I. A. Haddad; Shi-Zhong Yang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2008)

Phylogenetic Diversity of the Archaeal Community in a Continental High-Temperature, Water-Flooded Petroleum Reservoir - Hui Li; Shi-Zhong Yang; Bo-Zhong Mu (Current Microbiology, 2007)

Applications of conditional nonlinear optimal perturbation in predictability study and sensitivity analysis of weather and climate - Mu Mu; Wansuo Duan; Hui Xu; Bo Wang (Advances in Atmospheric Sciences, 2006)